First-Principles investigation of the Electronic and Optical Properties of Cs-Doped FAPbI3 Halide Perovskite Solar Cell (Journal of Innovative Research, 2025)
Despite their promising power conversion efficiency, formamidinium lead iodide (FAPbI3) perovskite solar cells have phase instability and moderate efficiency. Doping with cesium (Cs) has been demonstrated to improve the stability of the photoactive α-FAPbI3 phase as well as increase the efficiency. The effect of Cs doping on the electronic and optical characteristics of FAPbI3 is examined in this work using first-principles density functional theory (DFT) computations. Our findings demonstrate that the addition of Cs causes minor alterations in the electronic structure, such as shifts in the bandgap and adjustments to the effective masses. In addition, we examine the optical absorption characteristics of Cs-doped FAPbI3, offering information on how doping might affect device performance. Due to its 1.28 eV band gap, which is within the Shockley-Queisser limit, the 12.5% Cs-doped FAPbI3 is appropriate for use in tandem solar cells. These results provide useful theoretical direction for the logical design and optimization of stable and high-performing Cs-doped FAPbI3 perovskite solar cells.